Extension of rapid phase-contrast magnetic resonance imaging using BRISK in multidirectional flow - Hershey, Bradley L.; Doyle, Mark W.; Anayiotos, Andreas (My University, 2005)
We developed BRISK-CON-VPS, a rapid phase-contrast cine approach that is a hybrid of the BRISK-VPS (Block Regional Interpolation Scheme for k-space) and conventional (CONV-VPS) scanning employing k-space views per segment (VPS). BRISK-CON-VPS allows data acquisition approximately four times faster than CONV-VPS imaging and has the advantage compared to BRISK-VPS that it can potentially be incorporated into real-time applications. In BRISK-CON-VPS contiguous regions of k-space are sampled using a views per segment factor that is varied as a function of distance from the k-space center. Computational fluid dynamics (CFD) data were used to simulate CONV-VPS, BRISK-VPS, and BRISK-CON-VPS. BRISK-CON-VPS was simulated by incrementing the VPS progressively with increasing distance from the k-space origin while BRISK-VPS was simulated using a uniform VPS applied to the sparse sampling scheme. Simulations showed that up to a base VPS of 5, both BRISK-CON-VPS and BRISK-VPS retained excellent axial-velocity accuracy. Secondary in-plane velocity flow fields were well represented with BRISK-CON-VPS and BRISK-VPS up to a base VPS of 3. CONV-VPS, BRISK-CON-VPS, and BRISK-VPS were applied in vivo and shown to provide comparable quantitative flow data. BRISK-CON-VPS accomplishes breath-hold acquisitions as efficiently as BRISK-VPS, but without requiring data interpolation or under-sampling k-space.
Keywords: Hemodynamics; Cardiovascular system; Computer simulation; Magnetic resonance imaging